Empowering micro-entrepreneurs through community communication networks in Pangandaran’s tourism sector - Subekti, Priyo; Bakti, Iriana; Koswara, Aang (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Though micro-MSMEs are being more acknowledged as important engines of local economic growth, especially in tourism-oriented areas, there is still little knowledge of how community communication networks operate as tools of social empowerment, especially in settings characterized by internal migration, digital inequality, and resource asymmetry. This paper looks at how such networks enable indigenous and migrant micro-MSME players in Pangandaran, a fast-growing coastal tourism area in Indonesia. The study uses a qualitative case study method to grasp the complexity of community dynamics set against the background of unequal access to resources and possibilities among commercial actors. Data were gathered using in-depth interviews with 20 key informants and 4 community representatives, supplemented by participant observation and community document analysis. The research found, via thematic analysis, that communication networks are also platforms for empowerment by means of training, resource access, and social solidarity in addition to channels for corporate information exchange and promotion. Especially during the COVID-19 crisis, when tactics like product diversification and internet marketing became vital, these networks have supported corporate adaptation. Still, there are ongoing issues, including low digital literacy, unequal information access, and intra-community conflicts hindering group development. The results highlight the need to enhance community capacities by means of inclusive communication policies, digital literacy projects, and conflict resolution tools. Local governments, community-based organizations, and legislators trying to create strong and inclusive economic ecosystems in tourism-dependent areas will find these ideas useful.